Hip Arthroscopy in Traumatic Hip Dislocation: Literature review and two case reports - Promsang, MD, Trai; Sukcharoenyingyong, MD, Sittichoke; Kongrukgreatiyos, MD, Kitiphong; Kuptniratsaikul, MD, Somsak (Journal of Southeast Asian Orthopaedics, 2022)
Hip dislocations occur commonly in young adults from high-energy motor vehicle accidents. Injuries to the hip range from simple dislocation without a fracture to complex fracture of the acetabulum or femoral head/neck. Complications after traumatic hip dislocation are devastating. This injury may lead to prolonged disability and dysfunction from complications such as osteoarthritis (OA) and osteonecrosis. Osteoarthritis after traumatic hip dislocation occurs at a frequency of 24% to 54%. There was a report that demonstrated 24% of the simple hip dislocation patients developed osteoarthritis. The development of OA after hip dislocation is considered to be caused by residual intra-articular small bone or cartilage fragments. Several patients may have loose bodies within the joint that goes unrecognized and untreated. There is a high prevalence of intra-articular loose bodies despite negative plain radiographs and thin-cut CT scans. Direct arthroscopic visualization is the best way to demonstrate the intra-articular loose bodies and debris. The main purpose of this article is to review the role of hip arthroscopy in traumatic hip dislocations and a variety of traumatic hip injuries.